The Effect of Work Discipline, Organizational Culture and Work Environment on Employee Performance At PT. Bank SulSelBar Palopo Branch - Maq’ Firah Hakka; Haedar; Duriani (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This research aims to analyze the influence of work discipline, organizational culture and work environment on employee performance at PT. Bank Sulselbar Palopo Branch. By using a quantitative approach and multiple linear analysis techniques, the population used was 50 employees, where the entire population was sampled through census techniques with data collection methods using questionnaires. The research results show that (1) Work Discipline has a significant and influential effect on Employee Performance at PT. Bank Sulselbar Palopo Branch. (2) Organizational culture does not have a significant influence on employee performance at PT. Bank Sulselbar Palopo Branch. (3) The work environment has an influence, but not significantly, on employee performance at PT. Bank Sulselbar Palopo Branch.